asjo THE EFFECTIVENESS OF PINEAPPLE PEEL EXTRACT (Ananas comosus) AS A MOSQUITO REPELLENT FOR AEDES AEGYPTI - Rafiqi; Yuni Nindia, Yuni Nindia (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The Aedes aegypti mosquito is a vector of Dengue Hemorrhagic Fever (DHF). DHF vector control is carried out in various ways, including the use of insecticides and by using repellent. The use of chemical-based for mosquito repellents cause residues on the environment and endanger for health. Many studies have been carried out to find natural repellents derived from plants, one of them is by using pineapple peel extract. Pineapple peel extract contains flavonoid compounds, tannins, saponins which have the potential to repel mosquitoes and can kill mosquitoes.This study aims to determine the effectiveness of pineapple peel extract (Ananas comosus) as a mosquito repellent for Aedes aegypti. This research is an experimental study, using 180 Aedes aegypti mosquitoes with three treatments and three repetitions. Observation of the number of mosquitoes perched on hand bait was carried out every 5 minutes in the first hour and every hour for 4 hours. The data analyzed using the one-way ANOVA test. The results showed that the average number of mosquitoes perched at a concentration of 10% (18); at a concentration of 20% (16); and at a concentration of 30% (12). The higher the concentration used, less mosquitoes perched on hand. The results of the ANOVA test showed that there was an effect of pineapple peel extract on the number of mosquitoes that perched on hand (p <0.05). The LSD test showed that there was a significant difference in the number of mosquitoes perched between a concentration of 30% with a concentration of 10% and 20%. It can be concluded that pineapple peel extract (Ananas comosus) can be a repellent to reduce the number of mosquitoes that perch on hand bait.